Donor-appended sensitizers and further exploration of cobalt polypyridyl mediators: behavior and consequences in dye-sensitized solar cells - Ashbrook, Lance, author; Rappé, Anthony, advisor; Gelfand, Martin, committee member; Kennan, Alan, committee member; Ladanyi, Branka, committee member; Shores, Matthew, committee member (Colorado State University. Libraries, 2014)
Dye-sensitized solar cells (DSCs) have been thoroughly investigated over the past two decades as viable alternatives to traditional silicon solar cells. Fueling this research is the potential for DSCs to exhibit comparable efficiencies to silicon but at a fraction of the cost due to the generally cheaper materials employed. This dissertation presents studies conducted with cobalt polypyridyl mediators as substitutes for the more commonly employed I-/I3-. In addition, several novel sensitizers are synthesized incorporating electron donors in order to separate the injected electron and subsequent hole on the dye. Chapter 1 reviews a brief history of DSC development and the relevant processes in an operational cell. The interplay of these processes is discussed. Commonly employed materials are presented as well as alternatives used in the literature and in the work throughout this dissertation. Instrumentation and methods utilized throughout this work are also discussed. The use of copper polypyridyl dyes in DSCs is discussed in Chapter 2. While there is literature precedent for these materials as sensitizers, very few studies exist due to inherent issues to the sensitizers that are not shared with the more traditional ruthenium dyes. These problems are highlighted and discussed in the context of sensitizer design. One of the primary issues is the coordination of mediator additives to the oxidized copper center, rendering it unable to participate in further photoexcitation. Studies are presented that show the incorporation of a phenothiazine-type electron donor into the sensitizer results in rapid reduction of the copper center and prevents additional coordination. Electrochemical and cell testing studies are presented in Chapter 3 that partially explain why the addition of lithium ion to the mediator solution results in better DSC current values, particularly with cobalt mediators. The electrochemistry of the Co2+/3+ couple on FTO appears to be highly dependent on cations present in solution. Li+ present in solution results in current being "shut off" at the FTO surface. Thus, Li+ addition leads to an additional charge transfer resistance at the anode which leads to a reduction in undesired electron scavenging. Although platinum films or platinized FTO are the usual materials of choice for DSC cathodes, they generally perform better when used in conjunction with I-/I3-. The cobalt complexes employed as alternative mediators tend to exhibit more reversible electrochemistry on gold, but gold cathodes have historically been difficult to fabricate reproducibly. Chapter 4 probes a sulfide modification technique that appears to improve gold cathode performance. Based on the data presented, the mediator additive t-butyl pyridine weakly adsorbs to the gold surface which disrupts the electronic coupling with an oxidized cobalt complex. Modification with sulfide ion results in a lower charge transfer resistance at the surface which translates to a better fill factor. Finally, the last chapter further explores the use of incorporating a phenothiazine electron donor into the sensitizer. In this chapter, novel ruthenium dyes are synthesized and evaluated against some commonly employed sensitizers in the literature. The relevant processes are more difficult to elucidate in these systems than in the copper systems due to the similar absorption profiles of the Ru → ligand MLCT and oxidized phenothiazine. This makes the important technique of transient absorption more problematic to employ. Therefore, the effect of the donor is evaluated based primarily off cell testing data. The de-convolution of mass transport and donor effects is attempted by comparing with Z-907, which is a commonly used sterically demanding sensitizer. Additional experiments are also suggested which would offer more insight into this competition.
Keywords: copper; sensitizer; ruthenium; DSSC